Tinjauan Sistematis Pendekatan Terapi Spiritual Alquran pada Pasien Skizofrenia - Rosyanti, Lilin; Hadju, Veny; Hadi, Indriono; Syahrianti, Syahrianti (Health Information : Jurnal Penelitian, 2018)
Schizophrenia is a major psychiatric disorder characterized by changes in perception, thought, affect, and behavior. Some therapeutic approaches in schizophrenic patients are psychoreligious or psychospiritual therapy. Psychoreligious / psychospiritual therapy will generate self-confidence and a sense of optimism. These two things (self-confidence and optimism) are important for healing from a disease in addition to drug therapy and other medical measures. Al-Quran therapy is a healing therapy and solution for physical, spiritual and social diseases for Muslims. Listening to and reading the Qur'an scientifically has a calming effect, promotes relaxation, and eliminates negative physical and mental disorders, stimulates the release of endorphins in the brain, which has a positive effect on mood and memory, focuses on positive thoughts and experiences, distracts negative thoughts , reduce stress, anxiety, and depression, become a non-pharmacological treatment to complement existing therapies.